2012
DOI: 10.1089/neu.2009.0947
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Neurite Transection In Vitro

Abstract: In order to quantify degenerative and regenerative changes and analyze the contribution of multiple factors to the outcome after neurite transection, we cultured adult mouse dorsal root ganglion neurons, and with a precise laser beam, we transected the nerve fibers they extended. Cell preparations were continuously visualized for 24 h with time-lapse microscopy. More distal cuts caused a more elongated field of degeneration, while thicker neurites degenerated faster than thinner ones. Transected neurites degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…Our data suggests that in an isolated system of cortical neurons, rate of outgrowth may not be reliant upon microtubule dynamics. However, it has been reported that the regenerative response of cut axons is correlated with the length of the remaining stump (Gomis-Ruth et al, 2008;Cengiz et al, 2012). Thus it is plausible that by using the scratch injury model where numerous axons are severed at once could have important cofounders possibly masking drug effects on post-injury sprout length and outgrowth speed.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggests that in an isolated system of cortical neurons, rate of outgrowth may not be reliant upon microtubule dynamics. However, it has been reported that the regenerative response of cut axons is correlated with the length of the remaining stump (Gomis-Ruth et al, 2008;Cengiz et al, 2012). Thus it is plausible that by using the scratch injury model where numerous axons are severed at once could have important cofounders possibly masking drug effects on post-injury sprout length and outgrowth speed.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that axoplasmic compaction and subsequent axial collapse is more effective in thinner axons suggesting a potentially more effective cut-end sealing. Indeed we previously demonstrated that axons with smaller diameters tend to degenerate less [38]. The collapse may be passive due to lose of internal scaffold in most part, but may also depend, at least partially, on retained actomyosin contractility [18,39].…”
Section: Discussionmentioning
confidence: 97%
“…For this, the cell suspension was carefully pipetted on top of a three-layer percol (Sigma) gradient (60, 35 and 10% from bottom to top) prepared with NBA-B27 and spun at 3000g for 20 mins in a centrifuge cooled down to 4 0 C. The neurons that were collected from 35 % layer were washed with NBA-B27 and spun once more at 120 g for 3 mins then supernatant was discharted and pellet was re-suspended in 1 ml NBA-B27. (Cengiz et al 2012). The cell suspension were seeded on silicon (WPI-Dow-corning) coated glass dish and conditioned in incubator for 3 days (37 C 0 and 5% CO2).…”
Section: Methodsmentioning
confidence: 99%